An innovative search for pedagogical ideas in management - Lytvyn, S. (Problems of Engineer-Pedagogical Education, 2021)
Currently, there is a growing awareness of the need for education institutions and university teachers to modernize instructional tools in accordance with the changing socio-economic situation in the country, which, in turn, actualizes a search and development of new pedagogical concepts and technologies, as well as an innovative search for pedagogical ideas in management. At the time of the development of innovative processes in education, when many of them occur spontaneously, a special role and place should be occupied by the problems of transition of education institutions from the mode of formation and functioning to the mode of development. The article analyzes the aspect of formation and introduction of innovative methods in management. Peculiarities of formation and implementation of innovative methods in management in Ukraine are determined. The current state of formation and implementation of innovative methods in management in Ukraine is considered. The efficiency of introduction of innovative methods in management is analyzed. Suggestions for the formation and implementation of innovative methods in management in Ukraine are made. The modern world and, accordingly, all systems operating in it, need to implement such methods due to the vast opportunities in their applicability, which is, in turn, characterized by the improvement of internal factors and the elimination of inefficient management methods in the global system. The findings and results of the work made it possible to substantiate and develop proposals and recommendations for the formation and implementation of innovative methods in management, namely it was proved that competently applying certain innovative methods in accordance with the specifics of the system, one can achieve the following outcomes: an increase in the competitiveness of the system; optimization of the level of resource consumption; cost reduction: economic and human costs; an increase in the efficiency of the system; transition to a more progressive stage of development.